Efeito de diferentes frequências de manejos no temperamento de bovinos de corte - Ceballos Betancourt, Maria Camila [UNESP] (2014)
The aim of this study was to evaluate the effect of two different handling frequencies on beef cattle temperament kept on pasture; and to evaluate the association between the animals’ temperament and their daily weight gain under each management condition. 2,007 animals kept in the ‘frequent handling condition’ (MF) - characterized by using rotational grazing method with monthly managements in the corral were assessed; and compared to 1593 animals kept in the ‘less frequent handling condition’ (MPF) - characterized by using the alternate stock grazing method, and taken to the corral every six months. Three different temperament indicators were used for the assessment: 1) reactivity composed score (ECR); 2) flight speed (VS in m/s); and 3) qualitative behaviour assessment (QBA). The tests were held during the management in the corral on three commercial farms. The animals’ average daily weight gain (ADG) was calculated for one of the properties in both management conditions. Firstly a variance analysis was made, applying the GLM procedure from SAS. For the QBA, it was held a Factor Analysis, generating a temperament qualitative index (IQT) for each animal. For assessing the effect of the handling frequency on the QBA, it was applied the one-way ANOVA, which included the IQT as a dependent variable and the effect of handling frequency as an independent variable. To test the association between temperament and average daily weight gain (ADG), residual correlations of ADG with VS, ECR and IQT were obtained with the GLM (MANOVA) procedure from SAS for MPF condition. Hence, the handling frequency was used as a function, considering the groups as a fixed effect and the age of the animals at the time of evaluation as a linear effect covariable at this condition. For the MF condition, it was used The Pearson Correlation, since all the animals belonged to the same group, showing no ...